2020
DOI: 10.3332/ecancer.2020.1084
|View full text |Cite
|
Sign up to set email alerts
|

Impact of axillary node-positivity and surgical resection margins on survival of women treated for breast cancer in Ibadan, Nigeria

Abstract: Introduction: Oncologic surgical extirpation, the mainstay of loco-regional disease control in breast cancer, is aimed at achieving negative margins and lymph node clearance. Even though axillary lymph nodal metastasis is a critical index of prognostication, establishing the impact of lymph node ratio (LNR) and adequate surgical margins on diseasespecific survivorship would be key to achieving longer survival. This study examines the prognostic role of pN (lymph nodes positive for malignancy), LNR and resectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
10
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 34 publications
(50 reference statements)
4
10
2
Order By: Relevance
“…Most patients (98.9%) had a tumour ≥2 cm while 28.0% had tumours >5 cm. This is similar to what was reported by Ayandipo et al [ 19 ] in Ibadan, 93.3% of their patients had tumours ≥2 cm and 65.3% >5 cm in size. There are disparities in the size of the tumour at presentation in this study with that of the western world.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Most patients (98.9%) had a tumour ≥2 cm while 28.0% had tumours >5 cm. This is similar to what was reported by Ayandipo et al [ 19 ] in Ibadan, 93.3% of their patients had tumours ≥2 cm and 65.3% >5 cm in size. There are disparities in the size of the tumour at presentation in this study with that of the western world.…”
Section: Discussionsupporting
confidence: 91%
“…The study found the mean age of breast cancer patients to be 47.6 years (SD 11.2) which is consistent with the findings of Adesunkanmi et al [ 18 ] in Ile-ife and studies in Ibadan by Dairo et al [ 9 ] and Ayandipo et al [ 19 ]. Similar findings were also demonstrated from north eastern part of Nigeria at the University of Maiduguri Teaching Hospital [ 20 ] and Federal Medical Centre, Gombe [ 21 ].…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations